Coal ash foamed bricks stabilised with hydrated limeactivated GGBS (HL-GGBS) / Mohamad Ezad Hafez Mohd Pahroraji - Mohd Pahroraji, Mohamad Ezad Hafez (Institute of Graduate Studies, UiTM, 2017)
Coal-fired thermal power plant produces million tonnes of coal ash as an industrial by-product and is significant to be used as raw material for fabrication of bricks. Coal ash could potentially substitute the traditional materials i.e. clay and sand that were used to produce fired clay and cement sand bricks. Clay and sand were continuously extracted from depleting and dwindling non-renewable natural resources that could gradually degrade the environment in the long run. Meanwhile, lime and Portland cement are popular binding materials that could eventually damage and pollute the environment if continually used without control. Alternatively, ground granulated blastfurnace slag (GGBS), an industrial by-product could be used as substitution. However, GGBS requires activation in an alkaline environment for self-cementitious acceleration. For now, the reliable source of alkali is lime or Portland cement. Most researchers have used either fly ash or bottom ash as raw material and either lime or Portland cement as binder. There is also less evidence in effort to lightweight the bricks that were using industrial by-products as raw materials.